The Knowledge of Pregnant Women about Shortcomings of ‌Cesareanand Its Associated Factors in 2009 - Keramatollah Rahmanian; Vajiheh Rahmanian; Mitra Ghasvari (Golestan University of Medical Sciences, 2013)
Background and Objective: Cesarean section has some adverse effects on maternal and neonatal health . The knowledge of pregnant women about disadvantages of cesarean can affect on the use of cesarean delivery. The aim of this study is to determine the knowledge of pregnant women about disadvantages of cesarean section.   Material and Methods: In this descriptive study, we studied 360 pregnant women referring to obstetric and gynecology clinics, via convenience sampling. The women who were physicians or midwives were not assessed. We used a questionnaire including demographic part and eighteen questions about knowledge. The data were recorded by SPSS version 11.5 then analyzed by use of t- test and Chi square.   Results: The mean of knowledge is (12.23±4.0). There is a significant relation between knowledge and education level (p=0.008). But it is not significant for other variables (p>0.05).   Conclusion: In terms of our findings, the knowledge of pregnant women is not very good about cesarean disadvantages that it can affect on the selection of delivery type. Therefore, it is a necessity for health officials to perform appropriate programs to increase the knowledge about disadvantages of cesarean section.